APPLICATION OF ARCHITECTURAL KNOWLEDGE BASED GENETIC ALGORITHM AND FUZZY TOPSIS IN DECISION MAKING - C. Dhaya; R. Dhanalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
Architectural knowledge is important for the architecting process, as it improves the quality of the software architecture evaluation process and the architecture itself [18]. All the stakeholders need to obtain relevant architectural knowledge in making design decisions. It has been stated that the major challenge in assessing software design is an exact description of the quality characteristics and specific knowledge about the design decisions. Though many qualitative architecture assessment methods are available, a quantitative evaluation method is needed to evaluate the candidate architectures over a set of architectural design characteristics. Software architecture evaluation framework addresses the competing objectives of cost minimization and quality maximization between different architectural options. Due to the uncertainty in the judgment for design quality characteristics, architectural knowledge based fuzzy genetic algorithm framework is developed for accessing quality attributes is developed to assist the selection of the underlying architectural designs. A new multi-criteria decision making (MCDM) method , Architectural knowledge based fuzzy Genetic Algorithm and Technique for Order of Preference by Similarity to Ideal Solution(FGA-TOPSIS) is proposed to describe the quality requirements of the envisioned system which forms the basis for the comparison and selection criteria. Experimental results obtained indicate that FGA-TOPSIS can be used as a feasible and effective a multi criteria decision making approach for architecture selection under partial or incomplete information (uncertainty).